PERENCANAAN LANSKAP KALIURANG SEBAGAI KAWASAN WISATA TERPADU DI YOGYAKARTA - Togar LM Gultom; Afra DN Makalew; Nizar Nasrullah (Jurnal Lanskap Indonesia, 2018)
Kaliurang has tourism potential and become the third most visited tourist destination in Yogyakarta after Parangtritis Beach and Prambanan Temple. This potential can be used to make Kaliurang as one of the revenue sources of regional income. For that there should be an effort to maintain the sustainability of Kaliurang as a integrated tourist area. This study aimed to plan Kaliurang landscape as a integrated tourist destination area in Yogyakarta. This study was conducted in Kaliurang with an area of 339,56 ha. The method used in this study was planning method developed by Gold (1980). The results showed that Kaliurang has potential to be planned into integrated tourist destination with physical factors such as topography, climate, land cover, high biodiversity, and existing tourism conditions. Kaliurang as a tourist area has a high quality natural scenery but supply and demand aspects as a tourist area has still low. Kaliurang has an area with a value of tourist suitability for the development of tourism activities amounted to 238.97 ha and divided into two spaces, tourism object space and tourist support space with an area of 207.65 ha and 31.31 ha respectively. The tourist space has 9 theme activities and supporting tourist space has three theme activities. Keyword : Kaliurang, landscape planning, natural mountains, tourism, tourist destination area